2003
DOI: 10.3748/wjg.v9.i11.2413
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PLC-γ2 and PKCα in TPA-induced apoptosis of gastric cancer cells

Abstract: AIM:To investigate the roles of PLCγ2 and PKCα in TPAinduced apoptosis of gastric cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
5
25
0
Order By: Relevance
“…Similarly, the DEGS1 gene encoded a member of the membrane fatty acid desaturase family [57] and was proved to participate in the activation of caspase 9 and caspase 3, which were marker proteins of cell apoptosis [58]. Moreover, PLCG2 and PRKCE genes encoded phospholipase C-(PLC)γ2 and protein kinase C(PKC)-ε, respectively, and both proteins were important elements of cellular signal transduction pathways that could regulate a chain of events either in physiological or pathological status [59][60][61]. Kajstura found that angiotensinconverting enzyme (ACE) II could induce the translocation of PKC-ε of myocytes due to an increase in intracellular free Ca…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the DEGS1 gene encoded a member of the membrane fatty acid desaturase family [57] and was proved to participate in the activation of caspase 9 and caspase 3, which were marker proteins of cell apoptosis [58]. Moreover, PLCG2 and PRKCE genes encoded phospholipase C-(PLC)γ2 and protein kinase C(PKC)-ε, respectively, and both proteins were important elements of cellular signal transduction pathways that could regulate a chain of events either in physiological or pathological status [59][60][61]. Kajstura found that angiotensinconverting enzyme (ACE) II could induce the translocation of PKC-ε of myocytes due to an increase in intracellular free Ca…”
Section: Discussionmentioning
confidence: 99%
“…, which could lead to the initiation of apoptosis [62], while the translocation of PLC-γ2 was certified to transmit the TPA signal to its downstream molecule PKC and directly promote the process of apoptosis in MGC80-3 cells [59]. Analogously, NUAK1, also known as AMPKrelated protein kinase 5, was the downstream molecule of Akt, which participated in the classical signaling pathway with extensive consequences [63].…”
Section: +mentioning
confidence: 99%
“…Immunofluorescence analysis was performed as previously described (38). JEG-3 cells and PMTs were cultured in 1% oxygen or 21% oxygen for 24 h. The cells were washed with PBS (Sigma-Aldrich) and fixed in 4% paraformaldehyde.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…For example, in a study by Tomlinson et al (2001), PLCg2 was found to be essential for the Bruton's tyrosine kinase (BTK):ER-induced apoptosis response. Zhang et al (2003) also found that PLCg2 was significantly upregulated during TPA (12-O-tetradecanoylphorbol-1, 3-acetate)-induced apoptosis in gastric cancer cells, suggesting that PLCg2 has an essential role in the induction of apoptosis. However, little is known about the contribution of PLCg2 to the induction of apoptosis during LR.…”
Section: Introductionmentioning
confidence: 77%
“…These then activate downstream signaling pathways thus regulating various biological events, such as cell growth and differentiation (Ozdener et al, 2002). Recently, several studies have identified PLCg2 as an important regulator of apoptosis, and it has been reported to induce the apoptosis of gastric cancer cells (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%